Influence of titanium dioxide activated under visible light on survival of mold fungi - Daria Kądziołka; Paulina Rokicka; Agata Markowska-Szczupak; Antoni W. Morawski (Nofer Institute of Occupational Medicine, 2018)
Background In public and residential buildings, fungi are usually found in the dust or growing on building materials medium such. It has been known that a number of their spores may contaminate the indoor environment and deteriorate air quality in accommodation spaces. Previously designed air cleaning systems do not guarantee a complete removal of agents harmful to humans and animals. Therefore, there is a great need to develop a new solution to remove molds from indoor air. In recent years, photocatalysis based on titanium dioxide (TiO 2 ) has been proposed as an effective method for air pollutants removal. The aim of the study was to determine the effect of TiO 2 activated under artificial sun light (UV-VIS - ultraviolet - visible spectroscopy) on survival of fungi Penicillium chrysogenum and Aspergillus niger. Material and Methods The commercial P 25 (Aeroxide P 25, Evonik, Germany) and nitrogen modified titanium dioxide (N-TiO 2 ) were used. The microbiological study was performed using Penicillium chrysogenum and Aspergillus niger fungi. The survival of fungi was determined on the basis of changes in their concentration. Results It was found that N-TiO 2 has a stronger antifungal activity against P. chrysogenum and A. niger than P 25. For N-TiO2, the complete elimination of molds was possible after 3 h under artificial solar light activation. The minimal concentration of photocatalyst was 0.01 g×dm -3 ( P. chrysogenum ) and 0.1 g×dm -3 ( A. niger ). Conclusions The nitrogen modification of titanium dioxide produced expected results and N-TiO 2 presented good antifungal activity. The findings of the presented investigation can lead to the development of air filter to be used for removal of harmful agents (including molds) from indoor environment. Med Pr 2018;69(1):59-65